Evidence for a newly discovered triallelic pattern in the human STR D1S1656 locus - Vera Djeliova; Tsanko Markov; Stanislava Dimitrova-Nikolova; Dimo Krastev; Milka Mileva; Aleksandar Apostolov (Biotechnology & Biotechnological Equipment)
In this study, we report a case of a previously undetected triallelic pattern in the arrangement of structures at the D1S1656 locus in the Bulgarian population. The D1S1656 locus is one of the most widely used targets, present in almost all genetic analyses of DNA in forensic medical examinations. During routine forensic analyses for determining loci, we encountered a triallelic pattern in the genetic profile of biological materials from one individual. The samples were taken from a plastic cup and a bottle used by the suspect and were compared with seized material from the buccal mucosa by swabbing from the same individual. The results of the analyzed STR markers, performed using the PCR Amplification Kit, were compared with the nomenclature values of the analyzed STR markers contained in the AmpFlSTR NGM. We performed the identification with a confirmed genotype for the control DNA and compared with the control sample, in which the amplification product is missing. To better characterize the allele outside the allelic ladder of the size, we performed a re-extraction and re-amplification with the PowerPlex® Fusion 6 C System of the reference material from the registered individual. Analysis of the obtained results showed that the anomaly we observed belongs to the tri-allelic type I models. From the extensive review of the forensic literature, we found that such an anomaly has not been reported to date. This specific genetic anomaly confirmed the identification of the suspect and served the forensic scientists in solving the specific case.